Płyty Plastyczne pod Działaniem Sił Skupionych - Sokół-Supel, J. (Engineering Transactions, 1973)
The paper is concerned with the analysis of bending of plastic plates subjected to the yield condition of maximum principal moments. It contains the discussion of equations governing the problem and it formulates the boundary conditions. Admissible static and kinematic discontinuities are determined and the principles of construction of discontinuous fields of internal forces are outlined. Application of the method proposed made it possible to derive a number of completesolutions. The method presented makes it also possible to obtain statically admissible solutions. The procedure is illustrated by examples.